THE ROLE OF THE INTELLIGENCE UNIT OF THE INTAN JAYA POLICE IN HANDLING ARMED GROUPS IN THE INTAN JAYA DISTRICT AREA - Sigit Prasetyo, Tatag; Soekorini, Noenik; Ayuningtyas, Fitri; Hamdani, Fathul (Gapenas Publisher, 2025)
A Police Security Intelligence (Intelkam) acts as the